Advancing Digital Human Capital Through Talent Development in Postgraduate Higher Education - Muhammad Tahir Malik; Ali Hanafi; Asri; Mislia; Ifah Finatry Latiep (Global Research and Collaboration, 2026)
Quality of higher education, especially in postgraduate programs in the digital era. This study aims to analyze the talent development strategy of educators, identify supporting factors, and examine the obstacles faced in the development process at the Postgraduate Program of Megarezky University Makassar. The research uses a qualitative approach with phenomenological design. The research informants totaled 43 people consisting of 37 lecturers with doctoral degrees and 6 professors. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed using Miles and Huberman's interactive analysis model. The results of the study show that the development of educator talents is carried out through increasing academic and digital competence, strengthening research culture, developing academic collaboration, and supporting institutional policies. Key supporting factors include lecturers' intrinsic motivation, academic culture, supportive leadership, digital infrastructure, and collaborative networks. Meanwhile, the main obstacles include high administrative workload, limited research funding, digital competency gap, and lack of optimal international collaboration. This research emphasizes that the talent development of educators requires an integrated talent management system to improve the academic quality and competitiveness of universities in the digital era